Handbook of Ratings Approaches to Ratings in the Economy, Sports, and Society - Karminsky, Alexander; Polozov, Andrey (Springer International Publishing : Imprint: Springer, 2016)
This handbook presents a systematic overview of approaches to, diversity, and problems involved in interdisciplinary rating methodologies. Historically, the purpose of ratings is to achieve information transparency regarding a given body's activities, whether in the field of finance, banking, or sports for example. This book focuses on commonly used rating methods in three important fields: finance, sports, and the social sector. In the world of finance, investment decisions are largely shaped by how positively or negatively economies or financial instruments are rated. Ratings have thus become a basis of trust for investors. Similarly, sports evaluation and funding are largely based on core ratings. From local communities to groups of nations, public investment and funding are also dependent on how these bodies are continuously rated against expected performance targets.  As such, ratings need to reflect the consensus of all stakeholders on selected aspects of the work and how to evaluate their success. The public should also have the opportunity to participate in this process. The authors examine current rating approaches from a variety of proposals that are closest to the public consensus, analyzing the rating models and summarizing the methods of their construction. This handbook offers a valuable reference guide for managers, analysts, economists, business informatics specialists, and researchers alike.